Experiences, barriers and expectations regarding current patient monitoring systems among ICU nurses in a University Hospital in Lebanon: a qualitative study - Rayan, Ahmad; Al-Ghabeesh, Suhair H.; Fawaz, Mirna; Behar, Amal; Toumi, Amina (Frontiers in Digital Health, 2024)
The aim of the study is to assess the experiences, barriers, and expectations regarding current patient monitoring systems among intensive care unit nurses at one university hospital. Methods: A qualitative exploratory study approach was adopted to test the research questions. Results: intensive care unit personnel placed a high value on practical criteria such as user friendliness and visualization while assessing the present monitoring system. Poor alarm handling was recognized as possible patient safety hazards. The necessity of high accessibility was highlighted once again for a prospective system; wireless, noninvasive, and interoperability of monitoring devices were requested; and smart phones for distant patient monitoring and alert management improvement were required. Conclusion: Core comments from ICU personnel are included in this qualitative research on patient monitoring. All national healthcare involved parties must focus more on user-derived insights to ensure a speedy and effective introduction of digital health technologies in the ICU. The findings from the alarm control or mobile device studies might be utilized to train ICU personnel to use new technology, minimize alarm fatigue, increase medical device accessibility, and develop interoperability standards in critical care practice.Health care stakeholders may need to concentrate more on user-derived discoveries than top-down predictions in order to adopt more durable digital health technologies in the Intensive care unit. We may acquire health care professionals' trust by appreciating their ideas and implementing revolutionary methods by respecting their perspectives. The findings on alarm administration and portable devices in the ICU, in particular, could be used by healthcare institutions to brace ICU employees for digitalization, research facilities to decrease alarm fatigue, industry leaders to accept medical device functionality, and governmental organizations and decision makers to advance interoperability standards in critical care medicine. Other academics should be inspired by your results to perform qualitative patient-and user-centered studies in health care, particularly before inventing or applying hasty technical solutions.